Theory and applications of models of computation : 12th Annual Conference, TAMC 2015, Singapore, May 18-20, 2015, Proceedings /: 12th Annual Conference, TAMC 2015, Singapore, May 18-20, 2015, Proceedings. (2015) - Unknown
No abstract available